2019
DOI: 10.1038/s41396-019-0461-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent mixing of Vibrio parahaemolyticus populations

Abstract: Humans have profoundly affected the ocean environment but little is known about anthropogenic effects on the distribution of microbes. Vibrio parahaemolyticus is found in warm coastal waters and causes gastroenteritis in humans and economically significant disease in shrimps. Based on data from 1103 genomes of environmental and clinical isolates, we show that V. parahaemolyticus is divided into four diverse populations, VppUS1, VppUS2, VppX and VppAsia. The first two are largely restricted to the US and Northe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 43 publications
5
41
0
Order By: Relevance
“…Notably, some STs such as ST658 accounted for up to 4.59% of the total community, indicating that a few of the introduced V. parahaemolyticus populations had been established and fitted well in their new environment. This finding provides evidence supporting the hypothesis proposed by Yang et al that V. parahaemolyticus can multiply rapidly to constitute a substantial proportion of the bacteria in its new habitat ( 7 ). Thus, the transport of live aquatic animals deliberately delivered to distant farms in large quantities could have facilitated the transmission of bacteria among different regions or countries.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Notably, some STs such as ST658 accounted for up to 4.59% of the total community, indicating that a few of the introduced V. parahaemolyticus populations had been established and fitted well in their new environment. This finding provides evidence supporting the hypothesis proposed by Yang et al that V. parahaemolyticus can multiply rapidly to constitute a substantial proportion of the bacteria in its new habitat ( 7 ). Thus, the transport of live aquatic animals deliberately delivered to distant farms in large quantities could have facilitated the transmission of bacteria among different regions or countries.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study suggested that mixing of V. parahaemolyticus populations recently occurred ( 7 ). However, most investigated strains were collected from seafood or clinical samples and thus do not represent a defined epidemiological cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used ClonalFrameML [38] to infer the recombination events in L3b and L9 lineages as previously described [39]. The input maximum likelihood trees were constructed using FastTree V2 [37] based on the whole genome alignments, non-core sites were ignored during the calculation.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%